Asparagine endopeptidase regulates lysosome homeostasis via modulating endomembrane phosphoinositide composition - Linli Yao; GuangHui Zi; Miao He; Yuhong Xu; Lulu Wang; Baowei Peng (Cell Death and Disease)
Abstract Asparagine endopeptidase (AEP) is ubiquitously expressed in both physiological and pathological contexts, yet its precise role and functional mechanism in breast cancer remain elusive. Here, we identified increased AEP expression in breast cancer tissues, which correlated with poorer survival rates and a propensity for lung metastasis among breast cancer patients. Loss of AEP impaired colony formation by breast cancer cells in vitro and suppressed lung metastasis in mice. By Gene Set Enrichment Analysis (GSEA) analysis, we uncovered a positive association between aberrant AEP expression and autophagy as well as lysosomal function. Loss of AEP in breast cancer cells led to reduced autophagosome clearance and impaired lysosomal degradation. Mechanically, by co-immunoprecipitation and in vitro enzymatic cleavage assays, we identified the regulatory subunit p85 of class IA PI3K phosphatidylinositol 3-kinase (PI3K), as a substrate of AEP. Loss of AEP led to elevated endo/lysosomal PI3K activity and subsequent conversion of PtdIns(4,5)P2 (PIP2) to PtdIns(3,4,5)P3 (PIP3) on endo/lysosome membranes. Notably, the novel function of endo/lysosomal PI3K which was differently with its role in cytomembrane, was revealed by pharmacological inhibition with a potent endo/lysosomal PI3K inhibitor PIK75. PIK75 treatment showed increased vacuolar-ATPase assembly endo/lysosome membranes, prevented over lysosome perinuclear clustering/fusion and enhanced autophagosome clearance. Our findings demonstrate that AEP regulates cellular autophagy by modulating lysosomal function through its control over endo/lysosomal PI3K activity. These results suggest that AEP may serve as a potential target for suppressing metabolic adaptations in cancer.